INCIDENCE AND VISUAL OUTCOME OF ACUTE POSTOPERATIVE ENDOPHTHALMITIS - Narsani, Ashok Kumar; Nagdev, Partab Rai; Lohana, Mahesh Kumar; Jatoi, Shafi Muhammad; Gilal, Imtiaz (Journal of Ayub Medical College Abbottabad, 2011)
Objectives: To assess the incidence and visual outcome of acute post operative endophthalmitis treated by intravitreal antibiotics. Methods: This Prospective study was conducted at Department of Ophthalmology, Liaquat University Eye Hospital Hyderabad from November 2002 to October 2010. One hundred and nine patients of acute post operative endophthalmitis were treated with intravitreal antibiotics. The inclusion criteria of the patients was the clinical diagnosis of acute post operative endophthalmitis within 14 days of post operative period and visual acuity better than or equal to hand movement close to face. After enrolment, vitreous tap was carried out followed by intravitreal antibiotics injection. The outcome was measured in terms of clinical resolution of endophthalmitis and post resolution best corrected visual acuity. Results: Of the 109 patients 97 meet the criteria and followed completely were included. Sixty patients (61.9%) had extracapsular cataract extraction (ECCE) with posterior chamber intraocular lens implantation while phacoemulsification done in 37 (38.1%) patients. The visual acuity at presentation was 6/60 or worse in 80 (82.5%) patients. Vitreous tap was done in 86 (88.7%) patients. Vitreous biopsy yields an organism in 32 (33%) patients. Coagulase positive were the most common organism. 75 (77.3%) patients received single dose of intravitreal antibiotic. Forty five (46.4%) patients received single antibiotic, ceftazidime while two antibiotics given in 52 (53.6%) patients. Twenty five (25.8%) patients also had oral steroids. Ninety one (93.8%) patients responded to intravitreal antibiotics. Seventy five (77.32%) patients achieved final visual outcome better than 6/60 in meantime of 54.08 days. Six (6.2%) patients developed no perception of light and another six patients (6.2%) referred for vitrectomy. Conclusion: The final visual outcome of the patients with acute postoperative endophthalmitis is strongly associated with the visual acuity at presentation as well as type of infective organisms. Keywords: Endophthalmitis, visual outcome, intravitreal antibiotics